(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
The objective of this study was to determine the expected minimum number of sequence reads needed to achieve full coverage of the microbial species found in the gut of giant panda This was done by first, analyzing five different mammalian metagenomes namely horse, coyote, whitetail deer, humpback whale and the bottlenose dolphin as metagenomic references; based on an approximate of 1,000,000 sequence read estimation. After rarefaction analysis using MG-RAST Version 3.0 analysis pipeline, an average value of 775,075 reads was found to be sufficient for metagenomic analysis. Next, the fecal matter of giant panda was sampled at Zoo Negara, and DNA extraction was performed. DNA extraction was then subjected to DNA qualification and quantification analysis; where the results show that the samples are still viable and sufficient in yield to be used for library preparation. After library preparation, the samples were sequenced using IlluminaTM MiSeq® next generation sequencer. The results of this research serve as a foundation for further studies of the giant panda metagenome.